Cosmic rays with LOFAR 2.0 - what’s next? - Mulrey, K.; Bouma, Sjoerd; Buitink, S.; Corstanje, A.; Desmet, M.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Jhansi, V. B.; Karastathis, N.; Laub, Philipp; et al. (Proceedings of Science, 2024)
The LOFAR radio telescope has been used to measure radio emission from cosmic-ray air showers in the 1016.5−1018 eV range for over a decade. LOFAR is currently undergoing an upgrade (LOFAR 2.0) which will enable continuous observation and a tenfold increase in data rate, as well as a wider measurement bandwidth. We have recently doubled the size of the particle detector triggering array located at LOFAR to maximize the benefits of this upgrade. We are also developing new analysis techniques and data pipelines in order to best utilize the new influx of data and increase the energy range in which we measure. In this contribution, we present our plans for the LOFAR 2.0 cosmic-ray observation program.
CRIS-Team Scopus Importer:2025-02-04